Adsorption and Desorption Behavior of Branched Polymers with Hydrophobic, Hydrophilic, and Charged Side Chains - Wang, Xiujun (Langmuir : the ACS journal of surfaces and colloids, 2025)
The interfacial adsorption and desorption behavior of polymers and surfactants during chemical flooding plays a pivotal role in enhanced oil recovery (EOR), particularly in high-temperature, high-salinity (HTHS) reservoirs. The molecular topology (e.g., linear and branched) and functionality (hydrophobic (HB), hydrophilic (HL), negatively charged (NC) and/or positively charged (PC)) offer promising potential for improving the recovery efficiency of EOR. However, the relationship between polymer topology (or functionality) and interfacial behavior remains unclear. In this work, an extension of classical density functional theory, termed DFT-eTPT2, is used to systematically investigate the adsorption and desorption behavior of linear and branched functional polymers on a hydrophobic surface under HTHS conditions. The results show that HB-based binary copolymers with functional monomers (HL, PC or NC) are good candidates for the interfacial encapsulation of oil droplets and the migration of encapsulated oil-polymer aggregates into the aqueous phase. Specifically, a clear spatial segregation of monomers is observed, in which HB monomers promote interfacial adsorption, whereas HL, PC, and NC monomers facilitate detachment from the interface. Furthermore, their excess adsorption exhibits a nonmonotonic dependence on the bulk concentration of polymer (cp). Among these binary copolymers, the branched HB-based binary copolymer paired with PC monomers (B-HB-PC) exhibits optimal adsorption and desorption performance: the maximum excess adsorption around cp = 2.00 M; and the marked disparity in excess adsorption between the HB and PC side chains. However, beyond this degree of branching, the adsorption capacity declines sharply. This work provides molecular-level insight into the design of topological functional polymers, highlighting the importance of customized polymer architectures to maximize interfacial activity and oil recovery efficiency